Aplikasi Kompos Serasah Jagung Degan Bahan Pengkaya Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays saccharata Sturt) - Syafii, Muhammad; Ariani, Erlida; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Corn is the second of carbohydrate sources after rice that holding the most important role as a food source. Sweet corn is the one kind of corn that most people liked. This corn lifespan is early-ripening, have a high price and contain a high sugar that resulting as a business with a good prospects. The one ways that we can do to get a good productivity is with fertilizing. Fertilizing with organic compound such as compost can reduce the toxicity, plant nutrient buffer, repairing soil structure, increasing the efficiency of fertilizer, reducing the risk of erosion and helping on increasing supplied of macro and micro nutrient. This research aim is to get the best richer substance for corn manure compost that can support sweet corn (Zea mays saccharata Sturt) growth and productions. This research implementing experimentally used Complete Random Design, contain 5 treatments with 4 replications. The observing parameter is plant high, weight of dry plant, appearing of male flower, appearing of female flower, corn stem diameter, corn stem length, corn stem weight without husk per plot (g), analysis of C-organic, N, P and K contained on compost. The gained data analyzing used random analyzes and continued with Duncan test leveled 5 %. This research result showed that giving a corn manure as richer substance can increasing N, P and K of corn manure compost and give a same response at growth but it can increasing the sweet corn (Zea mays saccharata Sturt) productions. Keywords : Sweet corn, compost, richer substance